The Effect of Discipline on Learning Outcomes of Students of Class V SDN 161 Pekanbaru - Tia Nengsih; Siti Quratul Ain (IJoIS: Indonesian Journal of Islamic Studies, 2022)
This research is motivated by the existence of problems regarding discipline and student learning outcomes at SDN 161 Pekanbaru which are still relatively low and have not been carried out properly. This study aims to determine the effect of discipline on student learning outcomes at SDN 161 Pekanbaru. This type of research uses a quantitative approach with an ex post facto research design. The population of this study is class V, totaling 72 students. While the sample of this study used a saturated sampling technique, the research sample amounted to 72 students from class V. The data collection technique used a questionnaire sample, and documentation. Testing the instrument using validity and reliability. Data collection techniques are descriptive analysis and prerequisite tests, namely normality, homogeneity, hypothesis testing in the form of simple linear regression using the conditions Ha is accepted and Ho is rejected. Based on the research data processing, there is a significant influence between discipline on the learning outcomes of fifth grade students at SDN 161 Pekanbaru with the proof that the t-test results are greater than t-table (t-count > t-table) or (4,432>1.997). This means that the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected.